"Energetics of the outer retina II: Calculation of a spatio-temporal energy budget in retinal pigment epithelium and photoreceptor cells based on quantification of cellular processes". - Christina Kiel; Stella Prins; Alexander J E Foss; Philip J Luthert (PLoS ONE)
The outer retina (OR) is highly energy demanding. Impaired energy metabolism combined with high demands are expected to cause energy insufficiencies that make the OR susceptible to complex blinding diseases such as age-related macular degeneration (AMD). Here, anatomical, physiological and quantitative molecular data were used to calculate the ATP expenditure of the main energy-consuming processes in three cell types of the OR for the night and two different periods during the day. The predicted energy demands in a rod dominated (perifovea) area are 1.69 x 1013 ATP/s/mm2 tissue in the night and 6.53 x 1012 ATP/s/mm2 tissue during the day with indoor light conditions. For a cone-dominated foveal area the predicted energy demands are 6.41 x 1012 ATP/s/mm2 tissue in the night and 6.75 x 1012 ATP/s/mm2 tissue with indoor light conditions during daytime. We propose the likely need for diurnal/circadian shifts in energy demands to efficiently stagger all energy consuming processes. Our data provide insights into vulnerabilities in the aging OR and suggest that diurnal constraints may be important when considering therapeutic interventions to optimize metabolism.